Photocyclization of diarylethylenes with a boronate moiety: a useful synthetic tool to soluble PAH building blocks - Feofanov, Mikhail; Uka, Arber; Akhmetov, Vladimir; Amsharov, Konstantin (Photochemical & Photobiological Sciences, 2020)
The synthesis of ten ortho-fused PAHs bearing boronic pinacol ester groups (BPin) is reported. The products are obtained via modification of Mallory photocyclization in 45-99% yields. Among them are examples of highly strained molecules such as [4]helicene derivatives with BPin substituents in the cavity. The method allows double C-C coupling and tolerates more than one BPin functionality.
CRIS-Team Scopus Importer:2020-06-02